Transformation of chemically fine tuned zeolite A precursor into dense lithium aluminosilicates - a comprehensive phase evolution and sintering study - Selvaraj, Kaliaperumal (Microporous and Mesoporous Materials, 2010)
Beyond their conventional revelation as catalysts, zeolites are being perceived as more challenging materials for modern applications. Thermal recrystallization of zeolite precursors is an efficient method for the preparation of dense aluminosilicate ceramics. However, factors viz., nature of the precursor and the way of firing it etc., influence the product quality. The present report is a systematic and detailed account of a phase transformation of Li modified zeolite A precursor using powder X-ray diffraction (PXRD), thermogravimetry (TG), differential thermal analysis (DTA), scanning electron micrographs (SEM), atomic absorption spectroscopy (MS), energy dispersive X-ray (EDX) and density measurement techniques. It involves an amorphisation followed by a recrystallization into lithium aluminosilicate (LAS). A comprehensive correlation of PXRD, TG/DTA, SEM, EDX and density data explains the complexity of high temperature phase transition (25-1200 degrees C). A qualitative phase analysis revealed the mediation of formation of LAS ceramic, beta-spodumene by few satellite transitions of SiO(2). (C) 2010 Elsevier Inc. All rights reserved.
Keywords: LAS silicate; Phase evolution; Phase transformation; Powder XRD; zeolite